Loss of Radioactivity from Barium Carbonate Samples - Yankwich, Peter E. (Lawrence Berkeley National Laboratory, 1948)
The exchange loss of radioactivity from solid samplos of barium carbonate through the agency of carbonic acid and its ions has been investigated under a variety of conditions. It is concluded that the losses observed are greatly dependent upon the method of sample preparation, in particular the nature or any heat treatment which the sample materials undergo.